2022
DOI: 10.1101/2022.11.23.517109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Universal microbial reworking of dissolved organic matter along environmental gradients

Abstract: Soils are losing increasing amounts of carbon annually to freshwaters as dissolved organic matter (DOM), which, if degraded, can accelerate climate change. DOM is more susceptible to degradation closer to its source and becomes increasingly dominated by the same, difficult-to-degrade compounds as degradation proceeds. However, the processes underlying DOM degradation across environments are poorly understood. Here we found DOM changed similarly along soil-aquatic gradients irrespective of differences in enviro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…We then correlated commonly used descriptive traits of individual molecular formulae to the strength of the correlation between the relative intensity of each formulae and the HIX value of the corresponding DOM pool across all sampling times. Molecular formulae that were more positively associated with HIX also had larger values of the formula-based estimate of aromaticity (AI mod , ρ = 0.62, p <0.001), which indicates the presence of condensed aromatic structures 63 and confirms that stream DOM was becoming more like surface soil post-logging, confirmed by leaching studies performed at the site 43 . Studies in lake sediment have found that AI mod strongly correlates with the relative abundance of lignin-like compounds 59 , further supporting a terrestrial origin to the HIX signal rather than changes produced in-stream 60, 61 .…”
Section: Mainsupporting
confidence: 53%
See 2 more Smart Citations
“…We then correlated commonly used descriptive traits of individual molecular formulae to the strength of the correlation between the relative intensity of each formulae and the HIX value of the corresponding DOM pool across all sampling times. Molecular formulae that were more positively associated with HIX also had larger values of the formula-based estimate of aromaticity (AI mod , ρ = 0.62, p <0.001), which indicates the presence of condensed aromatic structures 63 and confirms that stream DOM was becoming more like surface soil post-logging, confirmed by leaching studies performed at the site 43 . Studies in lake sediment have found that AI mod strongly correlates with the relative abundance of lignin-like compounds 59 , further supporting a terrestrial origin to the HIX signal rather than changes produced in-stream 60, 61 .…”
Section: Mainsupporting
confidence: 53%
“…Finally, major ions, nutrients, and metal concentrations were measured from a subset of the sampled water at the Great Lakes Forestry Centre, Sault Ste. Marie, Ontario, according to methods outlined in ref 43 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with that of Schroeter et al who found that litter metabolomes converged over time in a lab-based decomposition experiment regardless of being derived from different sources. Others working in temperate forests and grasslands have similarly found that DOM from different sources converged as it passed through soils, and this has been attributed to microbial production and consumption of DOM over time . Our approaches could be used to assess the potential impacts of phototrophic biofilms on DOM molecular richness and persistence changes in paddy soils.…”
Section: Discussionmentioning
confidence: 79%
“…Others working in temperate forests 54 and grasslands 55 have similarly found that DOM from different sources converged as it passed through soils, and this has been attributed to microbial production and consumption of DOM over time. 56 Our approaches could be used to assess the potential impacts of phototrophic biofilms on DOM molecular richness and persistence changes in paddy soils.…”
Section: Characterization Of Spe−dom During Biofilm Growth and Decomp...mentioning
confidence: 99%